The Problem with Public University Salaries in Kenya - Munene, Ishmael I (International Higher Education, 2014)
Faculty strikes over salaries have become a regular feature in Kenya’s public universities. The article identifies the preponderance of union-negotiated pay increase, absence of a merit pay system and the lack of differentiated pay tied to institutional context as key contributing factors. It recommends a more robust compensation scheme that includes pay-for-performance system, context-based differentiated pay for university executives and the democratization of the university budget processes.